Meta-Analysis the Effect of Screen Time on the Risk of Overweight in Children and Adolescents in Asia - Nita Putriasti Mayarestya; Eti Poncorini Pamungkasari; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Overweight and obesity are a growing threat to the well-being of the world's children. In 2010-2016, the prevalence of underweight was growing rapidly among children and adolescents in Asia. With the development of technology, screen time has become a behavior that can have a negative effect on children and adolescents if it is associated with being overweight. One in three internet users in the world are children and adolescents under the age of 18 years. Asia has the highest rates of child internet use globally. Several studies in Asian countries reported high screen time in children and adolescents. On average, children and adolescents in Asia have screen time duration > 2 hours per day outside of study/school time. This study aims to analyze the effect of screen time duration on overweight children and adolescents in Asia.Subjects and Method: This research is a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: Google Schoolar, Science Direct, Researchgate and PubMed by selecting articles published in 2010-2021. “Screen Time” OR “Sedentary Behavior” AND “Overweight” OR “Body Mass Index” OR “BMI” OR “Weight” OR “Obesity” AND “Children” OR “Child” OR “Adolescent” OR “Teen” AND “Cross Sectional